osteoblogda

2021-12-31

Using the method of undetermined coefficients, find the general solution of the following differential equation

habbocowji

Beginner2022-01-01Added 22 answers

We find the general solution of eq (1) of the method of undesermened coefficient.

Now the aurilary eq for the homogenous eq

$y3{y}^{\prime}+2y=0$ is

${m}^{2}-3m+2=0$

$(m-2)(m-1)=0$

$m=1,2$

So the function$y={c}_{1}e+{c}_{2}{e}^{2x}$

Here we take${y}_{p}=A{x}^{2}+Bx+c$ ,

${y}_{p}=2a+b$

${y}_{p}2a$

Putting the value of$y}_{p},{y}_{p},{y}_{p$ in eq (1) we get

$2a-3(2ax+b)+2(a{x}^{2}+bx+c)={x}^{2}$

$2a-6ax-3b+2a{x}^{2}+2bx+2={x}^{2}$

$2a{x}^{2}+(-6a+2b)x+(2a-3b+2c)={x}^{2}$

$2a=1\Rightarrow a=\frac{1}{2}$

$-6A+2b=0\Rightarrow -6\times \frac{1}{2}+2b=0\Rightarrow -3+2b=0\Rightarrow b=\frac{3}{2}$

$2a-3b+2c=0\Rightarrow 2\cdot \frac{1}{2}-3\cdot \frac{3}{2}+2=0$

$\Rightarrow 1-\frac{9}{2}+2c=0$

$\Rightarrow 2c\cdot \frac{9}{2}-1$

$2c=\frac{1}{2}$

$=1c=\frac{1}{4}$

$y}_{p}=\frac{1}{2}{x}^{2}+\frac{3}{2}x+\frac{1}{4$

The general solution is

$y\left(x\right)={y}_{c}+{y}_{p}$

$={c}_{1}{e}^{x}+{c}_{2}{e}^{2x}+\frac{1}{2}{x}^{2}+\frac{3}{2}x+\frac{1}{4}$

Now the aurilary eq for the homogenous eq

So the function

Here we take

Putting the value of

The general solution is

Deufemiak7

Beginner2022-01-02Added 34 answers

Given differential equation is

$y3{y}^{\prime}+2y={x}^{2}+x+1$ (1)

$AE\text{}is\text{}{D}^{2}-3D+2=0$

$(D-1)(D-2)=0$

$\therefore D=1,2$

$\therefore CF={c}_{1}{e}^{x}+{c}_{2}{e}^{2x}$

PI is of the form

$y={A}_{0}+{A}_{1}x+{A}_{2}{x}^{2}$

${y}^{\prime}=0+{A}_{1}+2{A}_{2}x$

$y0+2{A}_{2}$

Substituting in (1)

$2{A}_{2}-3({A}_{1}+2{A}_{2}x)+2({A}_{0}+{A}_{1}x+{A}_{2}{x}^{2})={x}^{2}+x+1$

$\therefore 2{A}_{2}{x}^{2}+(2{A}_{1}-6{A}_{2})x+2{A}_{0}-3{A}_{1}+2{A}_{2}={x}^{2}+x+1$

Comparing the coefficients

$2{A}_{2}=1,2{A}_{1}-6{A}_{2}=1,2{A}_{0}-3{A}_{1}+2{A}_{2}=1$

Solving,${A}_{2}=\frac{1}{2},{A}_{1}=2,{A}_{0}=3$

$\therefore PI=3+2x+\frac{1}{2}{x}^{2}$

$\therefore GS=CF+PI$

$y={c}_{1}{e}^{x}+{c}_{2}{e}^{2x}+(3+2x+\frac{1}{2}{x}^{2})$

PI is of the form

Substituting in (1)

Comparing the coefficients

Solving,

Vasquez

Expert2022-01-09Added 669 answers

Solve

Homogen solution:

Particular solution:

Put his into the initial equartion to get A, B and C gives me:

This leads me to the answer:

However the correct answer is

Where's my miss? Where comes the last term from?

22+64

When a cold drink is taken from a refrigerator, its temperature is 5 degree C. After 25 minutes in a 20 degree C room its temperature has increased to 10 degree C. What is the temperature of the drink after 50 minutes?

How many minutes are there in $2\frac{3}{5}$ hours?

Find the answer for $64$ power $\frac{1}{6}$.

The following law describes the relationship between gas volume and pressure: ________. A)Boyle's law; B)Henry's law; C)Charles' law; D)Dalton's law

If an electric switch is open then no current flows through the circuit.

A)True;

B)FalseThe price elasticity of supply of a good is 0.8. Its price rises by 50 per cent. Calculate the percentage increase in its supply.

How many quarts are in 10 gallons?

When the net force acting on an object is zero, the total momentum of the system will:

A)remain constant;

B)increase with time;

C)decrease with time;

D)None of theseHow many centimeters are in four meters?

A notebook computer has a mass of 2.25 kilograms. About how many pounds does the notebook weigh?

If the dot product of two non-zero vectors is zero, then the vectors A)are parallel to each other. B)are perpendicular to each other. C)can have any orientation. D)are anti-parallel to each other.

Which is longer 5 miles or 10 kilometers?

9 grams is how many milligrams?

How to write $673.5$ in scientific notation?